2004
DOI: 10.1002/jsfa.1753
|View full text |Cite
|
Sign up to set email alerts
|

Effect of preharvest sprays containing calcium, magnesium and titanium on the quality of peaches and nectarines at harvest and during postharvest storage

Abstract: Peach and nectarine trees were foliar sprayed with a formulation containing Ca 2+ , Mg 2+ and Ti 4+ . Parameters related to fruit quality were evaluated at harvest, after 7-28 days of cold storage and after subsequent ripening for 4 days at 20 • C (shelf life). At harvest, treated fruits from both cultivars had higher weight and pulp firmness than control fruits, while no effect was observed for either colour, total soluble solid content (TSS) and titratable acidity (TA) or the time required to ripen on the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
1
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 33 publications
5
38
1
5
Order By: Relevance
“…Several researchers reported general increases in SSC of grapes during cold storage [Sabir et al 2011], due to gluconeogenesis pathway [Famiani et al 2009] or water loss [Li et al 2015]. About the calcium treatment, studies on various peach cvs, revealed that SSC was not markedly influenced by the preharvest calcium sprays [Crisosto et al 2000, Serrano et al 2004], most probably due to fruit tissue differences, such as hairiness, which may solely affect the entrance of calcium into the fruit. Berry TA content of non-treated pruning vine underwent a progressive decrease during storage.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several researchers reported general increases in SSC of grapes during cold storage [Sabir et al 2011], due to gluconeogenesis pathway [Famiani et al 2009] or water loss [Li et al 2015]. About the calcium treatment, studies on various peach cvs, revealed that SSC was not markedly influenced by the preharvest calcium sprays [Crisosto et al 2000, Serrano et al 2004], most probably due to fruit tissue differences, such as hairiness, which may solely affect the entrance of calcium into the fruit. Berry TA content of non-treated pruning vine underwent a progressive decrease during storage.…”
Section: Resultsmentioning
confidence: 99%
“…Relatively lower TA decrease courses, with a subsequent lower MI in calcite-treated grapes indicate that preharvest calcite sprays obviously restricted postharvest physiological senescence of grape berries during the prolonged storage. Exogenous applied calcium has been reported to reduce decay, delay ripening and extend postharvest life of various fresh fruits such as peaches and nectarines [Serrano et al 2004], apples [Siddiqui and Bangerth 1995] and kiwi fruit [Gerasopoulos et al 1996]. Yang et al [2010] studied the molecular mechanisms of calcium beneficial effects and isolated genes from tomato coding for calmodulin, a calcium specific protein and SR/CAMTA (Stress Responsive/CaM-binding Transcriptional Activator), a calmodulin-binding transcription factor.…”
Section: Resultsmentioning
confidence: 99%
“…The few results reported considering Mg mostly dealt with quality traits related to storability. Serrano et al (2004) conducted a trial with peach (Prunus persica (L.) Batsch) and nectarine (Prunus persica (L.) Batsch var. nucipersica (Suckow) C.K.…”
Section: Fruitsmentioning
confidence: 99%
“…Por esa razón, resulta difícil realizar recomendaciones a cerca de la firmeza óptima de recolección, ya que esta va a depender, además de la variedad, del manejo postcosecha al que va a ser sometida la fruta. Además del efecto de la maduración en la firmeza de la fruta de hueso, el almacenamiento en frío también puede dar lugar a una disminución de la firmeza de la pulpa (Serrano et al, 2004). Ahora bien, la severidad del ablandamiento depende del cultivar (Crisosto y Valero, 2006) y de la temperatura de almacenamiento (Aly et al, 1981).…”
Section: Fruta De Hueso: Melocotón Nectarina Y Albaricoqueunclassified
“…Estos valores obtenidos en recolección y tras el almacenamiento en frío coinciden con los reportados en la bibliografía para otras variedades (Serrano et al, 2004).…”
Section: Fruta De Hueso: Melocotón Nectarina Y Albaricoqueunclassified